80Se(n, γ) cross-section measurement at CERN n TOF. (October 2020) - Babiano-Suarez, V.; Aberle, O.; Alcayne, V.; Amaducci, S.; Andrzejewski, J.; Audouin, L.; Bacak, M.; Balibrea-Correa, J.; Barbagallo, M.; Bennett, S.; Berthoumieux, E.; Bosnar, D.; et al.
Abstract: Radiative neutron capture cross section measurements are of fundamental importance for the study of the slow neutron capture (s-) process of nucleosynthesis. This mechanism is responsible for the formation of most elements heavier than iron in the Universe. Particularly relevant are branching nuclei along the s-process path, which are sensitive to the physical conditions of the stellar environment. One such example is the branching at 79 Se (3.27 × 10 5 y), which shows a thermally dependent β -decay rate. However, an astrophysically consistent interpretation requires also the knowledge of the closest neighbour isotopes involved. In particular, the 80 Se(n, γ ) cross section directly affects the stellar yield of the "cold" branch leading to the formation of the s -only 82 Kr. Experimentally, there exists only one previous measurement on 80 Se using the time of flight (TOF) technique. However, the latter suffers from some limitations that are described in this presentation. These drawbacks have been significantly improved in a recent measurement at CERN n TOF. This contribution presents a summary of the latter measurement and the status of the data analysis.